Prevalence of gastrointestinal parasites in captive Bovidae at Zoo Negara - Nadarajah, Kasturi (2016)
Parasitic diseases constitute one of the major problems causing mortality in captive Bovidae. Thus a study on the prevalence of gastrointestinal parasites was investigated from various species of animals from the Bovidae family housed at Zoo Negara Malaysia. A total of 14 pooled fecal samples were collected randomly from 8 species from 5 genus which are Bos (6), Hippotraginae (2), Tragelaphus (2), Oryx (2), and Kobus (2). All samples were examined by direct wet mount preparation, formalin ethyl acetate concentration technique and permanent stains which are trichriome and giemsa. Intestinal parasites that were found in all species were Strongylids (21.4%), Moniezia sp. (14.9%), Capillaria sp. (7.1%), Cryptosporidium spp. (7.1%) and Entamoeba sp. (7.1%). All samples that were positive for helminths or protozoa were asymptomatic animals with low parasitic loads. Monitoring the gastrointestinal parasite of wild Bovidae in captivity is imperative in assisting zoo management in the formulation and implementation of preventive and control measures against the spread of infectious parasitic diseases among these animals within the zoo or to humans.